1996
DOI: 10.3382/ps.0750867
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Copper Level Affects Copper Metabolism During Lipopolysaccharide-Induced Immunological Stress in Chicks

Abstract: Two experiments were conducted to examine the effect of dietary Cu level on Cu metabolism during the acute phase response in broiler chicks with adequate (Experiment 1) or deficient (Experiment 2) Cu. Diets based on cornstarch and isolated soybean protein were used to formulate a basal diet, and basal diet plus either 5, 10, or 15 mg/kg additional Cu as either CuO or CuSO4. Each diet was fed to six pens of five chicks per pen (Experiment 1) or eight pens of five chicks (Experiment 2). Half of the chicks on eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 19 publications
6
26
1
1
Order By: Relevance
“…These data are in agreement with other investigations that found a reduction in growth and BW (Koh et al 1996;Xie et al 2000;Mireles et al 2005) in birds treated with LPS. In contrast, Parmentier et al (1998) and Cheng et al (2004) demonstrated that the effect of LPS injection on BW gain is strain-and timedependent.…”
Section: Discussionsupporting
confidence: 83%
“…These data are in agreement with other investigations that found a reduction in growth and BW (Koh et al 1996;Xie et al 2000;Mireles et al 2005) in birds treated with LPS. In contrast, Parmentier et al (1998) and Cheng et al (2004) demonstrated that the effect of LPS injection on BW gain is strain-and timedependent.…”
Section: Discussionsupporting
confidence: 83%
“…A protective function of this protein is associated with a transport of about 95% of copper plasma pool (Butler and Curtis 1977) which increased content was observed in our study in pigeon sera and in plasma of other birds following the LPS injection (Johnson et al 1993). This α2 globulin (Butler and Curtis 1977) is responsible for cellular membrane stabilization (Koh et al 1996), protection from excessive accumulation of activated oxygen radicals in phagocytic cells (Butler and Curtis 1977) and reversion a hypoferremia accompanying APR (Piercy 1979). In the last mechanism a significant role is played by iron-binding glycoprotein -Tf.…”
Section: Discussionmentioning
confidence: 99%
“…This rise was observed in our study following the first LPS injection in pigeons (endotoxin fever) what is a proof of the activation of important humoral compound of non-specific immune mechanisms (Gołąb et al 2002). Some cytokines are responsible for the stimulation of APP production in birds (Amrani et al 1986, Klasing et al 1987, Klasing and Johnstone 1991, Koh et al 1996. A depression of the cytokine production observed in response to repeated LPS injections could affect a fall in APP concentrations in conditions of pyrogenic tolerance in pigeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre elas, encontra-se a ceruloplasmina, secretada no fígado e considerada a principal proteína carreadora de Cu no soro (Koh et al, 1996), e a citocromo oxidase, uma metaloenzima fundamental para a transferência de elétrons para o oxigênio, uma etapa muito importante na respiração celular (Lehninger et al, 1995). O Cu induz a síntese da thionein no fígado, que consiste em uma seqüência de aminoácidos que varia conforme a espécie.…”
Section: Introductionunclassified